A Do Financial Distress and Accounting Conservarism Have Influence of Tax Avoidance with Leverage as a Moderating Variable - Jaunanda, Meiliana (AKRUAL: Jurnal Akuntansi, 2026)
Introduction/Main Objectives: This study discusses the effects of Tax Avoidance. The independent variables used in this research are Financial Distress and Accounting Conservatism. The dependent variable of this research is tax avoidance proxied by the Effective Tax Rate. The moderating variable in this study uses Leverage with Debt to Equity Ratio as a proxy, and there are Control Variables, namely Sales Growth, Age, Profitability, and Size. Background Problems: Financial distress is the cause of tax avoidance, because industries that are facing financial difficulties will look for ways to defend their companies and will avoid tax. Novelty: The researcher choose accounting conservatism and moderating leverage on this research . Research Methods: This study uses Manufacturing and Mining companies in Indonesia that are listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period and the data is taken from S&P Capital IQ. Finding/Results: Model I sample are (1) Leverage have a positive influence on Tax Avoidance. (2) Financial Distress and Accounting Conservatism has a negative effect on Tax Avoidance. Model II sample are (1) Financial distress and Moderation of financial distress and tax avoidance have a positive effect on Tax Avoidance. (2) Accounting Conservatism and Moderation Conservatism and tax avoidance have no effect on Tax Avoidance.. Conclusion: the first and second hypothesis was rejected and third hypothesis was accepted.